ANALISIS FAKTOR PENYEBAB CONTRACT CHANGE ORDER DAN PENGARUHNYA TERHADAP KINERJA PELAKSANAAN PROYEK KONSTRUKSI DI LINGKUNGAN PEMERINTAH KABUPATEN BADUNG - Dharmayanti, GAP Candra; Janasuputra, IMG Bayu; Wiryasa, Ngk. Md. Anom (JURNAL SPEKTRAN; Vol 9 No 2 (2021)DO - 10.24843/SPEKTRAN.2021.v09.i02.p06, 2021)
Badung Regency government has 116 activities in 2018 where there were 77.5% experiencing Contract Change Order (CCO) during construction phase. This study aimed to analyze the influential factors of CCO on the construction project performanceand to formulate prevention strategies. Data was collected by distributing questionnaires to 55 respondents. Data was analysed using RII and multiple linier regression methods. The most dominant factor causing the occurrence of CCO was the discrepancy between the project designand the field condition, as indicated bythe RII value of 0.735. The multiple linear regression analysis demonstrated that there were 5 dominant factors (the best predictors) that affect the project performance.  Among the 5 factors, the discrepancy between the project design and the project field condition was indictaed as the most influential factor on the overall project performance in term of quality, cost and time. Based on separate regression analysischanges in the project work scopeor the project additional volume of work  become the most influencing factors to the project quality.Strategies for preventing  CCO was formulated based on interview with the experts, that cover conducting field survey to complete the required data, using BIM software to provide accurate volume of work, and  synchronizing planning document  to ensure the project design fulfilled the requirement of the building users.